Cannabis use, sexual behaviors, and HIV prevention behaviors among young adults attending key-population-led sexual health clinics in Bangkok, Thailand: A mixed-method study - Pongkwan Yimsaard; Kathryn E. Lancaster; Thunchanok Ratchatasitthigul; Rena Janamnuaysook; Kritima Samitpol; Nittaya Phanuphak; Somporn Saiwaew; Jeremy L. Ross; Arunrat Tangmunkongvorakul (PLoS ONE, 2026)
Background The intersection of cannabis and sexual behaviors poses important public health concerns, particularly following Thailand’s cannabis decriminalization. However, evidence on how cannabis use relates to sexual and HIV prevention behaviors among young adults in this policy context remains limited. This mixed-methods study aimed to assess cannabis use patterns and their associations with sexual behaviors and HIV prevention behaviors among young adults attending key population-led sexual health clinics in Bangkok, Thailand. Methods A self-report survey of 200 participants aged 18–24 assessed cannabis use, sexual behaviors, and HIV prevention behaviors using study-specific questionnaires, and the Cannabis Use Disorder Identification Test-Revised. Laboratory data, including HIV and Sexually Transmitted Infections (STIs) test results were extracted from medical records. Chi-square tests and Poisson regression examined associations between cannabis use, sexual behaviors, and HIV prevention behaviors. In-depth interviews with 15 cannabis users and 15 non-users explored perceptions of cannabis use in relation to sexual behaviors and HIV prevention behaviors to complement quantitative findings. Thematic analysis was conducted. Results Among the 200 participants (mean age = 21.45, SD = 1.89; 35% gay men, 32% transgender women), 22% were past-month cannabis users. Cannabis use was significantly associated with sex under the influence of any substances (Prevalence Ratio (PR)=1.24, 95%CI: 1.09,1.41), and alcohol (PR = 1.12, 95%CI: 1.02,1.24). No associations were found with other sexual behaviors, PrEP adherence, HIV or any STIs test results. Many participants cited disinhibitions as a pathway to risk, whilst some cannabis users emphasized individual responsibility as a more important determinant of behavior. Conclusions Cannabis use is linked to alcohol- or substance-influenced sex. Diverging views on cannabis and sexual risk suggest a need for tailored youth-centered harm reduction strategies within sexual health clinics that address risks and empower personal responsibility, particularly in the context of Thailand’s evolving cannabis policy.